Meningkatkan Kemampuan Manajemen Usaha pada Pelaku UMKM di Desa Situ Gadung Kabupaten Tangerang - Sari, Shella Puspita; Abdullah, Abdullah; Astuti, Aprilia (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This community service activity aimed to enhance business management skills among Micro, Small, and Medium Enterprises (MSMEs) actors in Situ Gadung Village, Tangerang Regency. The background of this program is the limited managerial knowledge and skills among local MSME entrepreneurs, which hinder their business growth and sustainability. The purpose of this activity was to improve the participants' capabilities in managing their businesses effectively through targeted training and interactive learning methods. The activity was conducted on May 4, 2025, in Situ Gadung Village. It was carried out by a team of 12 lecturers from Universitas Pamulang. Participants consisted of 19 MSME entrepreneurs and 7 general community members. The program included material presentation, practical exercises, discussions, and Q&A sessions to facilitate active learning and skill development. The results showed a significant improvement in participants’ understanding of business management concepts and their ability to apply these skills in their daily business operations. Participants reported increased confidence and motivation to implement better management practices, contributing to the potential growth of their enterprises.